Transformation of Cultural Arts Education in Indonesia: Combining Technological Innovation and Adaptability in the Era of Globalisation - Karoso, Subianto (Universitas Nahdatul Ulama Surabaya, 2024)
This research explores the transformation of arts and culture education in Indonesia in the face of challenges and opportunities brought about by globalisation and technological advancement. The main focus is on the integration of technology in arts education as a catalyst for pedagogical innovation. A qualitative descriptive method was used, with a sample that included schools, education experts, art teachers, and students. Data were collected through interviews, case studies, document analysis, and observation. The results showed that cultural arts education in Indonesia requires a transformation that involves not only the use of technology, but also the adaptability of curricula and teaching methodologies that are responsive to global needs and trends. The integration of technology has been shown to increase student engagement and participation, as well as providing them with opportunities to explore arts and culture in more interactive and innovative ways.